Retrospective study on the effect of adding heparin sodium saline at different time points on improving severe coagulation in dialyzers (不同时间点追加肝素钠盐水对透析器重度凝血改善作用的回顾性研究) - LI Linyang (李林洋); WANG Xinhui (王新慧); LI Hao (李昊); HUANG Yanping (黄砚萍); YU Renhuan (余仁欢) (中西医结合护理)
Objective To investigate the improvement effect of adding heparin sodium saline at different time points on the occurrence of severe dialyzer coagulation in maintenance hemodialysis (MHD) patients during dialysis. Methods Patients who underwent MHD treatment at the dialysis center of Xiyuan Hospital from November 2021 to November 2022 and experienced severe coagulation with dialyzers within 2 hours of treatment were included in the study. Electronic medical records were consulted to collect baseline data, data on various dialysis parameters, and relevant case records. According to the time point of adding heparin sodium, it was divided into two groups: the treatment group and the control group. Both groups were treated with 200 mL of physiological saline first, while the treatment group was treated with 1 mL of 625 U/mL (5 mg/mL) heparin sodium saline added to the dialysis machine heparin pump before re infusion of blood, and a maintenance dose of 1 mL/h was given until the dialysis was stopped 30 minutes before the end of dialysis; The control group received the same dose of heparin sodium salt solution added by the same method after re inducing blood. Compare the improvement effect of two sets of processes on severe coagulation dialyzers. Results A total of 12 MHD patients were included in this study. The treatment group consisted of 6 patients who completed 4 hours of normal dialysis treatment, while the control group consisted of 4 patients who completed normal treatment, and 2 patients who returned to the machine early due to severe coagulation in the dialyzer and vascular system. After dismounting, the coagulation level was evaluated. In the treatment group, 4 patients with no coagulation were classified as 0 level; Two patients had grade 1 coagulation on the dialyzer. In the control group, two dialyzers showed grade 3 coagulation, and there were small amounts of clots in both the arterial and venous ampulla; Three dialyzers showed grade 2 coagulation; One dialyzer showed grade 1 coagulation. There was a statistically significant difference (P＜0. 05) in the evaluation of coagulation grade between the two groups. Conclusion The method of adding heparin sodium saline before re infusion of blood can effectively alleviate the severe coagulation condition of the dialyzer, restore the function of dialyzer, and avoid blood loss, which is better than the method of adding heparin sodium saline after re infusion of blood to start extracorporeal circulation. (目的 探究不同时间点追加肝素钠盐水对维持性血液透析(MHD)患者透析中发生透析器重度凝血的改善作用。方法 纳入2021年11—至2022年11月中国中医科学院西苑医院透析中心进行MHD治疗, 在治疗开始2 h内发生透析器重度凝血的患者, 查阅电子病历收集患者基线资料、透析中各参数资料、相关病例记录。根据追加肝素钠的时间点分为治疗组和对照组两组。两组均采用先回冲200 mL生理盐水, 治疗组采用再次引血前通过透析机肝素泵追加浓度为625 U/mL(5 mg/mL)的肝素钠盐水1 mL并给予维持量1 mL/h, 直至透析结束前30min停止; 对照组采用再次引血后通过同种方法追加相同剂量肝素钠盐水。比较两组流程对重度凝血透析器的改善作用。结果 本研究共纳入12例MHD患者, 治疗组6例患者均完成4 h正常透析治疗, 对照组中4例完成正常治疗, 2例因透析器及血管路重度凝血提前回血下机。下机后凝血等级评估, 治疗组中, 4例患者无凝血为0级; 2例患者透析器1级凝血。对照组中, 2例透析器为3级凝血, 动脉壶、静脉壶均存在少量凝血块; 3例透析器为2级凝血; 1例透析器为1级凝血。凝血等级评估经比较两组存在统计学差异(P＜0. 05)。结论 于再次引血前追加肝素钠盐水的方法, 可以有效缓解透析器重度凝血的状况, 恢复透析器的功能, 避免血液丢失, 优于再次引血开始体外循环后再追加的方式。)